Type 1 Diabetes Mellitus and Premature Coronary Artery Disease - Dyah Ayu Ikeningrum; Djanggan Sargowo; Novi Kurnianingsih; Anna Fuji Rahimah (Universitas Brawijaya, 2022)
Cardiovascular disease, which affects more than half of all diabetics, is the leading cause of morbidity and mortality in patients with type 1 and type 2 Diabetes Mellitus (DM). Around 55% of diabetes patients are thought to have it, in comparison to 2-4% of the general population. A significant risk factor for the development of Coronary Artery Disease (CAD) exists in people with Type 1 Diabetes Mellitus (T1DM). However, it is worth noting that the present Models of risk prediction for T1DM have a variety of flaws. CAD risk is expected to double or quadruple over the next two to four decades, and diabetes mellitus is the third most significant risk factor for the etiology of illness. As a result, diabetes increases the chance of developing Acute Coronary Syndromes (ACS), whose incidence surpasses 20% after seven years, compared to a rate of 3.5 percent in non-diabetics – a rate comparable to individuals who have already experienced an Acute Myocardial Infarction (AMI). Additionally, it is crucial to identify any well-defined specific risk factors for T1DM as well as any extra subclinical atherosclerosis that may influence these patients at an advanced stage of disease progression. T1DM patients have more severe lesions, a lower left ventricle (LV) ejection fraction, a higher risk of cardiac events, and a higher rate of silent ischemia when compared to non-diabetics. They continue to have impaired microcirculation and endothelial function, both of which contribute to tissue perfusion problems.